Comparison among parents of special needs and healthy children on their motivation and expectations of their child's proposed orthodontic treatment: A pilot study - Joo Ming, Cheong; Abu Bakar, Noraini (2022)
Background: Special needs children present with challenging malocclusions that may not only affect their facial aesthetics, but also masticatory and speech function. There is an increasing awareness of malocclusion among special needs children and their parents. To date, there was no study comparing the motivations and expectations between parents of special needs and healthy children on the proposed orthodontic treatment.